2015
DOI: 10.1186/s40168-015-0126-1
|View full text |Cite|
|
Sign up to set email alerts
|

The first microbial environment of infants born by C-section: the operating room microbes

Abstract: BackgroundNewborns delivered by C-section acquire human skin microbes just after birth, but the sources remain unknown. We hypothesized that the operating room (OR) environment contains human skin bacteria that could be seeding C-section born infants.ResultsTo test this hypothesis, we sampled 11 sites in four operating rooms from three hospitals in two cities. Following a C-section procedure, we swabbed OR floors, walls, ventilation grids, armrests, and lamps. We sequenced the V4 region of the 16S rRNA gene of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 26 publications
(29 reference statements)
3
92
0
2
Order By: Relevance
“…Konya et al [31] showed an association between the bacteria found in house dust and in the infant. Due to the finding that infants born via C-section acquire a skin-like bacterial microbiome at birth, Shin et al [32] recently examined the dust found in the operating room at the time of C-section and found that the dust contains deposits of human skin bacteria. The role of this possible environmental exposure on the infant still needs to be further explored.…”
Section: Environmentmentioning
confidence: 98%
“…Konya et al [31] showed an association between the bacteria found in house dust and in the infant. Due to the finding that infants born via C-section acquire a skin-like bacterial microbiome at birth, Shin et al [32] recently examined the dust found in the operating room at the time of C-section and found that the dust contains deposits of human skin bacteria. The role of this possible environmental exposure on the infant still needs to be further explored.…”
Section: Environmentmentioning
confidence: 98%
“…Vertical transmission of bacteria from the body and breast milk of the mother to her infant has gained attention as an important source of microbial colonization (14, 1921) in addition to the microbial organisms obtained from the wider environment (22, 23), including the delivery room (24). Results from early cultivation-based and cultivation-free methods (16S rRNA community profiling and a single metagenomic study) have indeed suggested that the mother could transfer microbes to the infant by breastfeeding (25) and that a vaginal delivery has the potential of seeding the infant gut with members of the mother’s vaginal community (11, 14, 26, 27) that would not be available via caesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…Initial colonists are acquired maternally and from the immediate environment, but early life clinical factors (such as birth by cesarean section and neonatal antibiotic administration) can disrupt the normal acquisition process (Ding and Schloss 2014;Bäckhed et al 2015;Mueller et al 2015). Among premature infants, who generally harbor microbial communities of limited diversity and instability Sim et al 2013;Ward et al 2016), this disruption can lead to colonization by resident microbes of the neonatal intensive care unit (NICU) (Brooks et al 2014;Shin et al 2015).…”
mentioning
confidence: 99%